Ubiquitination Regulators Discovered by Virtual Screening for the Treatment of Cancer - Song, Ying-Qi; Wu, Chun; Wu, Ke-Jia; Han, Quan-Bin; Miao, Xiang-Min; Ma, Dik-Lung; Leung, Chung-Hang (Frontiers in Cell and Developmental Biology, 2021)
The ubiquitin-proteasome system is responsible for protein degradation in the cell in order to regulate various critical processes, such as DNA repair and cell cycle control. Ubiquitination can serve as a marker for mutation, chemical damage, transcriptional or translational errors, and heat-induced denaturation. However, aberrant ubiquitination and degradation of tumor suppressor proteins may result in the growth and metastasis of cancer. Hence, targeting the ubiquitination cascade reaction has become a potential strategy for treating malignant diseases. Meanwhile, computer-aided methods have become widely accepted as fast and efficient techniques for early stage drug discovery. This review summarizes ubiquitination regulators that have been discovered via virtual screening and their applications for cancer treatment.